Using Six Sigma to improve once daily gentamicin dosing and therapeutic drug monitoring performance. Issue 12 (7th August 2012) - Egan, Sean; Murphy, Philip G; Fennell, Jerome P; Kelly, Sinead; Hickey, Mary; McLean, Carolyn; Pate, Muriel; Kirke, Ciara; Whiriskey, Annette; Wall, Niall; McCullagh, Eddie; Murphy, Joan; et al.
Abstract : Background: Safe, effective therapy with the antimicrobial gentamicin requires good practice in dose selection and monitoring of serum levels. Suboptimal therapy occurs with breakdown in the process of drug dosing, serum blood sampling, laboratory processing and level interpretation. Unintentional underdosing may result. This improvement effort aimed to optimise this process in an academic teaching hospital using Six Sigma process improvement methodology. Methods: A multidisciplinary project team was formed. Process measures considered critical to quality were defined, and baseline practice was examined through process mapping and audit. Root cause analysis informed improvement measures. These included a new dosing and monitoring schedule, and standardised assay sampling and drug administration timing which maximised local capabilities. Three iterations of the improvement cycle were conducted over a 24-month period. Results: The attainment of serum level sampling in the required time window improved by 85% (p≤0.0001). A 66% improvement in accuracy of dosing was observed (p≤0.0001). Unnecessary dose omission while awaiting level results and inadvertent disruption to therapy due to dosing and monitoring process breakdown were eliminated. Average daily dose administered increased from 3.39 mg/kg to 4.78 mg/kg/day. Conclusions: Using Six Sigma methodology enhanced gentamicin usage process performance. Local process related factors may adversely affect adherence to practice guidelines for gentamicin, a drug which is complex to use. It is vital to adapt dosing guidance and monitoring requirements so that they are capable of being implemented in the clinical environment as a matter of routine. Improvement may be achieved through a structured localised approach with multidisciplinary stakeholder involvement.